Customer innovativeness in the adoption of Islamic banking in Malaysia - Latip, Malisah (John Wiley and Sons, 2024)
Islamic banking is a financial system that operates in accordance with Islamic principles, prohibiting the payment or receipt of interest (usury) and adhering to Shariah law. In order to ensure ethical and socially responsible financial practices, Islamic banks use profit and loss-sharing arrangements rather than traditional interest-based transactions. Islamic banking has gained substantial traction in Malaysia, driven by its alignment with the values of the predominantly Muslim population. However, the adoption of Islamic banking products and services still faces challenges related to consumer preferences and innovation attributes. This study investigates the mediating influence of customer innovativeness in the adoption of Islamic banking within the Malaysian settings. The study gathered responses from 436 respondents in Malaysia. Structural equation modelling was used to examine customer innovativeness's role in mediating the relationship between relative advantage, compatibility, observability and complexity and the intention to adopt Islamic banking. The study supports the hypotheses that customer innovativeness partially mediates the relationships between relative advantage, compatibility and observability of Islamic banking and the intention to adopt them. However, the study did not provide evidence for the mediation hypothesis concerning the complexity of Islamic banking. In conclusion, this study sheds light on the mediating role of customer innovativeness in Islamic banking adoption, aiding academia's understanding of consumer behaviour. Policymakers can use these insights to promote ethical financial practices, whereas the banking sector can adapt offerings to meet consumer preferences and enhance competitiveness.